Managing uncertainty: Hierarchies, markets and "networks" in the Russian timber industry. 1991-1998 - Barbara Lehmbruch (Bank of Finland, Institute for Economies in Transition (BOFIT), 1999)
The paper investigates institutional development in the Russian forestry sector after 1991.As it argues, while there has been a great degree of decentralization, original market-oriented reform blueprints for the industry, were only partially implemented.The reasons for this can be found largely in the failure of weak state institutions to standardize and universalize transactions.Attempts to restore topdown, Moscow-centered branch administration in the form of a state committee have equally failed.The paper asks how best to describe the highly personalistic transactional landscape that has emerged from the failure of hierarchies and markets.It argues that there is little evidence of "clan"-style "directors' networks" based on direct personal trust.Rather, economic actors prefer a two-pronged strategy of dealing with environmental uncertainty: While attempting to minimize environmental exposure by establishing forms of vertical integration, they also they hedge their exposure by maintaining multiple, often loose outside affiliations.This, it is argued, applies to both the horizontal, business-to-business level and to vertical clientelistic relations with state actors.
URN:NBN:fi:bof-201408072106
Keywords: 330; Russia; timber industry; organizations